IMPLEMENTATION OF AVIATION SAFETY CULTURE TO PREVENT FLIGHT ACCIDENTS AT HALIM PERDANAKUSUMA AIR FORCE BASE JAKARTA (Malaysian Management Journal, 2025)
This study aims to identify and analyze of safety culture in organizations of aviation sector through risk management analysis, the role of leadership in building a safety culture, self-assessment and implementation of aviation safety culture. This research was conducted at Halim Perdanakusuma Air Force Base Jakarta. Data collection was conducted using interviews, observation, questionnaires, and documentation study methods. The analysis technique used the Hazard Identification, Risk Assessment and Risk Control method scheme to identify Software, Hardware, Environment, Liveware and Liveware element based on AS/NZS 4360:2004, safety leadership dimensions, and safety culture dimensions by ECAST. The results of risk management analysis indicate that flight activities at Halim Perdanakusuma Air Force Base Jakarta show moderate and low risk values. The risk values of the environment and lifeware elements are yellow zone (moderate), the hardware and software element are green zone (low). The leadership role in safety culture has been implemented based on an analysis of 17 dimensions of safety leadership which is 13 dimensions (76.5%) have been running "Well", namely belief, awareness, commitment, attitude and behavior, priority, decision, agenda, resources, spirit of the movement, active involvement, tradition, appreciation, and performance. While 4 dimensions (35% to 70%) have been running "Quite Well" are monitoring and follow-up, values, and policy socialization. Self-assessment of safety culture implementation using 6 dimensions, that is commitment, behavior, awareness, adaptability, information, and justness, have a Level-4 Cooperating, shows that all staffs are engaged to develop cooperation and commitment to improving safety. Overall shows that Halim Perdanakusuma Air Force Base Jakarta has implemented a safety culture to reduce flight accidents and supports national priority programs in flight safety.